ANALISIS KEY PERFORMANCE INDICATOR (KPI) JARINGAN TELEKOMUNIKASI GSM PADA PT. HUTCHISON 3 INDONESIA (H3I) PONTIANAK - Khusnul Khotimah . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2017)
ABSTRACT- The development of GSM technology is expected to be able to accommodate data and voice services. Therefore the application of the GSM network is necessary to perfect design and optimization of the network, so that it can produce optimal  network  and  profitable.  Network performance measurement is performed to determine network performance at PT. Hutchison 3 Indonesia (H3I) Pontianak on the Khatulistiwa Plaza area without  and with  repeater. Drive Test is required to collect the data from the measurement of signal quality of a network. GSM network performance is analyzed based on KPI parameters are call statistics obtained using TEMS software, KPI parameters consist of CSSR, CSR and CDR. The results of Drive Test does not use repeaters obtained CSSR 100%, CSR 80% and the CDR of 20%, whereas when using a repeater obtained CSSR 100%, CSR 97% and CDR 3%, the data retrieval process performed three times with the result was not optimal, it caused kind of repeaters are using do not compatible with Node B frequency. Node B to the 3G network is 2100 MHz, while the repeater is work at frequency 1800 MHz. The result of using repeater for this network, performance states are in good condition. Keywords: Network performance, drive test, CSSR, CSR, CDR.